Implementasi kurikulum 2013 dalam pembelajaran maharah kitabah di Ma’arif Sukun 2 Malang - Achmad, Hildan Achmad (Maliki Interdisciplinary Journal, 2024)
MadrasahaIbtidaiyahaMa’arifaSukun 2 Malang has used curriculum 13 in Maharah Kitabah learning. This study describes the implementation of curriculum 13 in Maharah Kitabah learning at MI Ma’arif Sukun 2 Malang. The purpose of this study is to describe how the implementation of curriculum 13 in Maharah Kitabah learning is used at MI Ma’arif Sukun 2 Malang and how the impact of implementing curriculum 13 is in Maharah Kitabah learning. This type of research method is a descriptive qualitative research. Types of case studies conducted by interview and observation methods, and documentation. In the observation method, researchers observed the teaching and learning process of Maharah Kitabah at MI Ma’arif Sukun 2 Malang. In the interview method, the researcher interviewed Arabic teachers and grade 5 students for the 2022/2023 school year at Madrasah Ibtidaiyah Ma’arif Sukun 2 Malang. The results of this study are, 1. Implementation of the 2013 curriculum in Maharah Kitabah learning at Madrsah Ibtidaiyah Ma’arif Sukun 2 Malang, in the learning process that has been ongoing, the materials and books used are adapted to the components of the 2013 curriculum that have been determined by the Indonesian Ministry of Religion. Which emphasizes more on the three aspects, namely producing students with good morals (affective), skills (psychomotor), and knowledge (cognitive) that are sustainable. So it is hoped that students will be more creative, innovative and more productive. 2. The impact of its application is in accordance with procedures and easy to understand, they are complete in Maharah Kitabah subjects.